COMPLEXATION OF Zr (IV) WITH SOLID-PHASE XYLENOL ORANGE AND THEIR ANALYTICAL APPLICATION: UDC 543.064:543.42:541.183 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The chemistry of Zr (IV) complexing with the xylenol orange in solid – phase has been considered. Conditional constant of solid – phase complex stability has been calculated. The obtained theoretical data were used for development of a new procedur for zirconium determination.
Keywords: -